Sabotage in Tournaments with Heterogeneous Contestants: Empirical Evidence from the Soccer Pitch. (16th September 2013) - Deutscher, Christian; Frick, Bernd; Gürtler, Oliver; Prinz, Joachim
Abstract In this paper, we address the problem of sabotage in tournaments with heterogeneous contestants. In a first step, we develop a formal model, which yields the prediction that favorites exert higher productive effort, while underdogs are more tempted to engage in destructive actions (sabotage). This is because favorites have a higher return on productive effort and both types of effort are substitutes. In a second step, we use data from German professional soccer to test this prediction. In line with the model, we find that favorite teams win more tackles in a fair way, while underdog teams commit more fouls.